Kai kurie autorinės teis ė s ir mokslinės informacijos klausimai - Dagytė-Juodpusienė, Anda (Knygotyra, 2026)
Posibilities of securing scientific research with information are being viewed in the article as w ell as juridical status of information worth. Creative work of the author and information process are mentioned in accordance with union republic legislature (with standarts of copyright).